Measuring progress in availability and readiness of Basic emergency obstetric and newborn care (BEmONC) services in Bangladesh, 2014–2017 - Abu Sayeed; Nondo Saha; Ema Akter; Md. Mehedi Hasan; Anita Pickard; Anindita Saha; Abu Bakkar Siddique; Aniqa Tasnim Hossain; Shafiqul Ameen; Sabrina Jabeen; Tanjeena Tahrin Islam; Lubna Hossain; et al. (PLoS ONE, 2025)
Increasing the availability and readiness of basic emergency obstetric and newborn care (BEmONC) services is essential for improving maternal and neonatal health. However, little is known about any progress made in the availability and readiness of BEmONC services in Bangladesh. Using nationally representative data from the Bangladesh Health Facility Survey conducted between 2014 and 2017, we measured changes in the availability and readiness of BEmONC services in health facilities in Bangladesh, calculating the BEmONC service availability and readiness scores according to the World Health Organization Service Availability and Readiness Assessment guideline. The percentage of health facilities performing all seven basic signal functions declined slightly from 13% in 2014 to 11% in 2017. The decline was largely noticed in Maternal and Child Welfare Centers, Upazila Health Complexes, and Union Subcenter/Rural Dispensaries, as well as in all divisions except Rangpur. No remarkable changes in overall readiness of health facilities across location, division and facility type were observed between 2014 and 2017. However, significant reductions in availability and readiness were noticed when item-specific assessment was made. Type of health facility was significantly associated with both availability and readiness scores in adjusted regression models. Appropriate strategies and efforts could improve the availability and readiness of BEmONC services in health facilities in Bangladesh.